The Eastern Question as a Moral Question: European Order, Political Compromise, and British Policy Towards the Greek Revolution (1821–1828). Issue 2 (4th March 2023) - Mens, Jay
Abstract: This article examines British foreign policy towards the Greek Revolution (1821–1828), with a particular focus on the policies of Lord Castlereagh and George Canning. It uses Henry Kissinger's 1954 scheme of the 'statesman' and 'prophet' to examine the intellectual antagonism between the Greek policies of Castlereagh and Canning. While Castlereagh saw the Greek Revolution as a threat to the principles consecrated at the Congress of Vienna, Canning saw the Revolution in isolation, not in relation to other European insurrections. While Castlereagh was willing to allow the war to continue rather than risk the principles underpinning the European order, Canning was willing to compromise those principles for peace in Greece. The debate that surrounded these policies further drew the Greek cause into a broader matrix of political associations: conservatives backed the Ottoman Empire while liberals opposed it, reflecting the dispositions of both towards the political status quo in Britain and in Europe. The article argues that the dialectics that their two approaches represented—universal and systemic versus particular and contingent, and order versus peace—became recurrent themes in British policymaking throughout the Eastern Question.